Pengaruh Jenis Pelarut Dan Rasio Bahan Dengan Pelarut Pada Metode Ultrasonikasi Terhadap Aktivitas Antioksidan Ekstrak Daun Beluntas (Pluchea indica Less) - Krisma Widya Saraswati, I Gusti Ayu; Suter, I Ketut; Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2021)
This research was to determine the effect of type of solvent and the ratio of material to the solvent with ultrasonication on antioxidant activity of beluntas leaf extract ( Pluchea indica Less) and also determine the right type of solvent and the ratio of material to the solvent to extract beluntas leaves with the highest antioxidant activity. The complately Randomized Design (CRD) with 2 factors was used in this study. First factor is the types of solvents with 4 level (aquades, methanol 90%, ethanol 90%, acetone 90%) and second factor is the ratio of materials to solvent with 3 level (1:10, 1:15, 1:20). The treatment were repeated twice for obtain 24 experimental units. Variables observed were yield, total flavonoids, total tannin, antioxidant activity and IC 50 . The data were analyzed using variance and if the treatment had a significant effect, on was followed by the Duncan Multiple Range Test. The results showed that the interaction between the types of solvents and the ratio of material to the solvent had a very significant effect (P <0.01) on yield, total flavonoids, antioxidant activity, IC 50 , but the interaction have no real effect on the total tannin only show the very significant effect against solvent type and ratio on total tannin. The results showed that ethanol 90% with a ratio of 1:20 was the best treatment that produced antioxidant activity of 67.03 %, IC 50 of 74.37 ppm, total flavonoid of 11.08 mg QE/g, total tannin of 7.78 mg TAE/g and  yield of  4.16%.